Organic carbon uptake and mineralization in slow sand filters and their relation to process variables - Bayan Khojah; Salima Sadeghi; Lubos Polerecky; Jack J. Middelburg; Dick van Oevelen; Marcel T.J. van der Meer; Thilo Behrends (Journal of Water Process Engineering, 2025)

Exploring carbon dynamics in a slow sand filter using stable isotopes - Bayan Khojah; Salima Sadeghi; Lubos Polerecky; Jack J. Middelburg; Dick van Oevelen; Marcel T.J. van der Meer; Thilo Behrends (Water Research, 2025)

Efficient chemical and microbial removal of iron and manganese in a rapid sand filter and impact of regular backwash - Signe Haukelidsaeter; Alje S. Boersma; Lina Piso; Wytze K. Lenstra; Niels A.G.M. van Helmond; Frank Schoonenberg; Erik van der Pol; Luis C.C. Hurtarte; Paul W.J.J. van der Wielen; Thilo Behrends; Maartje A.H.J. van Kessel; Sebastian Lücker; et al. (Applied Geochemistry, 2024)

Impact of iron addition on phosphorus dynamics in sediments of a shallow peat lake 10 years after treatment - Melanie A. Münch; Rianne van Kaam; Karel As; Stefan Peiffer; Gerard ter Heerdt; Caroline P. Slomp; Thilo Behrends (Water Research, 2024)

Transport-limited kinetics of phosphate retention on iron-coated sand and practical implications - Victoria Barcala; Alraune Zech; Leonard Osté; Thilo Behrends (Journal of Contaminant Hydrology, 2023)

Coupled dynamics of iron, manganese, and phosphorus in brackish coastal sediments populated by cable bacteria - Martijn Hermans; Marina Astudillo Pascual; Thilo Behrends; Wytze K. Lenstra; Daniel J. Conley; Caroline P. Slomp (Limnology and Oceanography, 2021)
Coastal waters worldwide suffer from increased eutrophication and seasonal bottom water hypoxia. Here, we assess the dynamics of iron (Fe), manganese (Mn), and phosphorus (P) in sediments of the eutrophic, brackish Gulf of Finland populated by cable bacteria. At sites where bottom waters are oxic in spring, surface enrichments of Fe and Mn oxides and high abundances of cable bacteria were observed in sediments upon sampling in early summer. At one site, Fe and P were enriched in a thin layer (~ 3 mm) just below the sediment–water interface. X‐ray absorption near edge structure and micro X‐ray fluorescence analyses indicate that two‐thirds of the P in this layer was associated with poorly crystalline Fe oxides, with an additional contribution of Mn(II) phosphates. The Fe enriched layer was directly overlain by a Mn oxide‐rich surface layer (~ 2 mm). The Fe oxide layer was likely of diagenetic origin, formed through dissolution of Fe monosulfides and carbonates, potentially induced by cable bacteria in the preceding months when bottom waters were oxic. Most of the Mn oxides were likely deposited from the water column as part of a cycle of repeated deposition and remobilization. Further research is required to confirm whether cable bacteria activity in spring indeed promotes the formation of distinct layers enriched in Fe, Mn, and P minerals in Gulf of Finland sediments. The temporal variations in biogeochemical cycling in this seasonally hypoxic coastal system, potentially controlled by cable bacteria activity, have little impact on permanent sedimentary Fe, Mn, and P burial.

Coastal hypoxia and eutrophication as key controls on benthic release and water column dynamics of iron and manganese - Wytze K. Lenstra; Martijn Hermans; Marie J.M. Séguret; Rob Witbaard; Silke Severmann; Thilo Behrends; Caroline P. Slomp (Limnology and Oceanography, 2021)
Continental shelves are a major source of iron (Fe) and manganese (Mn) to marine waters. Here, we investigate controls on benthic release of Fe and Mn and the impact on the water column in the Baltic Sea. We find high in situ benthic release rates of dissolved Fe and Mn at seasonally hypoxic sites (bottom water oxygen between 0–63 μ mol L −1 ) receiving high inputs of organic matter. We find that benthic Fe and Mn release is sensitive to bottom water oxygen concentrations. Benthic Fe release is likely additionally controlled by Fe–sulfur redox chemistry in the surface sediment. For Mn, benthic release correlates positively with Mn oxide availability in the surface sediment. Benthic release contributes to high dissolved Fe and Mn concentrations in the water column and is amplified by repeated cycling of Fe and Mn between the sediment and overlying water through benthic release, oxidation in the water column, deposition as metal oxides, followed by reductive dissolution. Most water column Fe (∼ 80%) is present in particulate form near the seafloor. In contrast to Fe, a large percentage of the Mn remains dissolved (∼ 50%). We show that easily reducible Fe and Mn oxides are key forms of particulate Fe and Mn in suspended matter. The Baltic Sea represents a highly eutrophic, low oxygen end‐member when compared to other modern coastal systems. Our results imply that, upon continued eutrophication and deoxygenation of the coastal ocean, benthic release of dissolved Fe and Mn from continental shelves could become greater than previously thought.

Phosphorus Cycling and Burial in Sediments of a Seasonally Hypoxic Marine Basin - Fatimah Sulu-Gambari; Mathilde Hagens; Thilo Behrends; Dorina Seitaj; Filip J. R. Meysman; Jack Middelburg; Caroline P. Slomp (Estuaries and Coasts, 2018)

Dissolution of biogenic silica from land to ocean: Role of salinity and pH - Socratis Loucaide ,; Philippe Van Cappelle; Thilo Behrends (Limnology and Oceanography, 2008)
The dissolution rates of diatom frustules, phytoliths, two diatomaceous lake sediments, a siliceous ooze from the Southern Ocean, a diatomite deposit, and a synthetic amorphous silica were measured in flow‐through reactors supplied with either seawater or freshwater. Although the rates varied by more than one order of magnitude among the different siliceous materials, for any given solid the rate was systematically higher in seawater than freshwater, on average by a factor of five. Flow‐through reactor experiments with the diatom frustules and synthetic silica using mixtures of freshwater and seawater indicated that most of the rate increase occurred for seawater fractions between 0 and 50%. The observed rate enhancement is attributed to the higher pH of seawater and the catalytic effect of seawater cations on the hydrolysis of siloxane bonds at the silica surface. Because of their abundance in seawater, Na + and Mg 2+ are mainly responsible for the salinity‐induced rate increase. The large difference in dissolution kinetics between freshwater and seawater helps explain the very efficient recycling of biogenic silica in marine environments compared with freshwater lakes. Enhanced dissolution at the land‐ocean transition of biogenic silica produced by terrestrial plants and freshwater diatoms may represent a significant, but largely overlooked, source of nutrient silicon for estuarine and nearshore marine ecosystems.

What do acid-base titrations of live bacteria tell us? A preliminary assessment - Jaqueline Claessens; Thilo Behrends; Philippe Van Cappellen (Aquatic Sciences, 2004)